2022
DOI: 10.3389/fenvs.2022.995984
|View full text |Cite
|
Sign up to set email alerts
|

Government innovation support for green development efficiency in China: A regional analysis of key factors based on the dynamic GMM model

Abstract: Local government innovation support (LGIS) is an exogenous pulling force for high-quality economic development. Accurately identifying the mechanism by which LGIS affects green development remains practically and theoretically significant for building a long-term framework for driving green development. Based on provincial panel data (2010–2019), this paper uses the Super-SBM model to measure the green development efficiency (GDE) of different provinces in China. A dynamic panel GMM model is constructed to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…A study by Erdoğan et al (2020) for G20 countries found that the continuous increase in innovation expenditure in the industrial sector has had a signi cantly inhibiting implication on CO 2 emissions. In line with the ndings of Khattak et al (2022), government innovation support can reduce CO 2 emissions and improve green development e ciency in China. On the contrary, using the CCEMG estimation technique, Khattak et al (2020) examined complex in uences on carbon emissions in BRICS countries and found that innovative activities had a mitigating effect, but only on Brazil's CO 2 emissions.…”
Section: Green Innovation and Co 2 Emissionsmentioning
confidence: 61%
“…A study by Erdoğan et al (2020) for G20 countries found that the continuous increase in innovation expenditure in the industrial sector has had a signi cantly inhibiting implication on CO 2 emissions. In line with the ndings of Khattak et al (2022), government innovation support can reduce CO 2 emissions and improve green development e ciency in China. On the contrary, using the CCEMG estimation technique, Khattak et al (2020) examined complex in uences on carbon emissions in BRICS countries and found that innovative activities had a mitigating effect, but only on Brazil's CO 2 emissions.…”
Section: Green Innovation and Co 2 Emissionsmentioning
confidence: 61%
“…The Chinese government has exercised its financial and regulatory authority when allocating resources such as government grants, tax relief, innovation funds and license issues, actively encouraging innovation [11,12]. Among these government interventions, subsidies and tax incentives are the most significant for the state to foster domestic innovation and guide the economy's sustainable growth [13,14].…”
Section: Introductionmentioning
confidence: 99%